Synthesis of a Calix[4]arene‐Monodiazonium Salt for Surface Modification. Issue 46 (16th November 2018) - Malytskyi, Volodymyr; Troian‐Gautier, Ludovic; Mattiuzzi, Alice; Lambotte, Sarah; Cornelio, Benedetta; Lagrost, Corinne; Jabin, Ivan
Abstract : Reduction of calix[4]arene‐tetradiazonium salts at the vicinity of a surface, notably a carbon surface, leads to the formation of a dense and robust covalently bound monolayer. To expand the versatility of this unique methodology, the efficient synthesis of a calix[4]arene bearing a single diazonium group and thus a single anchoring point was achieved. The introduction of the diazonium group was developed through an original approach involving a copper‐catalyzed reaction for the preparation of an intermediate azido‐calixarene. The grafting ability of the calix[4]arene‐monodiazonium cation was evaluated by investigating its electrochemical reduction at glassy carbon electrodes. Studies of the blocking properties of the modified surfaces toward redox probes evidenced the formation of compact covalently bound layers at the carbon substrates, opening interesting perspectives in the field of surface modification by calixarene‐based diazonium salts. Abstract : The efficient synthesis of a calix[4]arene‐monodiazonium salt is described. The electrografting of this new compound on glassy carbon electrodes leads to a compact covalently bound calix[4]arene layer.